(3GWGQ ebJQM dJWHjb eaghe GdSjWQI hGdJMce dRjGOI aYGdjI GdeQGLYI GdOGNdjI ai bWGY GdHfhc GdJLGQjI ai eUQ (B: s (3OQGSI ebGQfI (B= A proposed framework for applying corporate governance concept to increase the effectiveness of internal auditing in the commercial banking sector in Egypt,A comparative study / s - (3MSf GHQGgje UGdMs; (3Ydi GMeO Rjf (B: s ((3GdbGgQI (B: s (3MSf GHQGgje UGdM (B: s, 2007)
(3JgOa GdOQGSI HUaI GSGSjI Gdi GbJQGM GWGQ deaghe GdMhceI ai GdHfhc GdJLGQjI jQGYi ajg edGAeJI ddHjFI GdeUQjI hPdc ef NdGd GdGSJaGOI ef GdOQGSI GdebGQfI ddeHGOF hGdbhGYO GdUGOQI ai eLGd GdMhceI eeG jJWdH Jbjje GdhVY GdeWHb ai GdHjFI GdeMdjI eY GjVGM JCKjQ gPG Gdeaghe Ydi aYGdjI fTGW GdeQGLYI GdOGNdjI(B. (3hdf jJfGhd GdHGMK JMdjd GdhGbY GdMGdi ddeQGLYI GdOGNdjI ai GdHfhc GdJLGQjI MjK Gf gPG GdLGfH jeKd OQGSI HMO PGJgG jecf GLQGDgG ai GdeSJbHds
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI MdhGf (B- (3cdjI GdJLGQI (B- (3bSe GdeMGSHIs
Keywords: (3bWGY GdHfhc GdJLGQjIs; (3GdeQGLYI GdOGNdjIs; (3eaghe GdSjWQIs